Self-governmental interpretations of tax law provisions - Brolik, Jacek (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The issuing of interpretations by bodies of a territorial self-government which act as tax interpretation organs, in a normative field of their performance as tax bodies, justifies the general naming of these interpretations: self-governmental interpretations of tax law provisions. In the range of issuing individual interpretations by self-governmental tax bodies, apart from giving them in art. 14j § 1 of the Polish tax law a status of tax interpretation bodies, the binding law stipulates, in relation to legal regulations of chapter 1a section II of the Polish tax law, some peculiarities and specific features in the range of: interpretation subject, application for and proceedings to be issued an interpretation, which have been discussed in this paper.